(untitled) (Fiep Bulletin - online, 2015)
The aim of this study was to draw a profile of people with cerebral palsy in physiotherapic care at the Centre for Disability (CADEF) and create criteria to meet as many factors as age, functional diagnosis, prognosis gear, school attendance, type of disabilities, related disabilities, early physical therapy treatment and frequency to physical therapy treatment. The present study was justified by the need to analyze the growing demand for people with cerebral palsy on the waiting list of CADEF. This study was descriptive, qualitative in nature with documental analysis of the physiotherapic assessment of 11 patients with cerebral palsy in CADEF. It was found that the profile of people with Cerebral Palsy in physiotherapy in CADEF present mostly spastic tetraparesis functional diagnostics, do not attend any form of school education, have related disabilities such as physical, mental and changes in speech and begin physical therapy treatment after one year of age making them ineligible to treatment. However, by presenting gait prognosis and undertake physiotherapic treatment at least once a week, these factors favor rehabilitation.